Imaging odisha - Kulke, H. (New Delhi : Prafulla, 2013)
maging Odisha in two volumes encompasses studies of history, religion, sculpture and architecture, art, music, and literature of Odisha, which represents one of the richest and oldest traditions in the Indian subcontinent. Prominent scholars Irom around the world have tried to expand and deepen our understanding of its cultural landscape even lesser known aspects stand illuminated.
Index 446-450p.; Contributors 451-454p.
Keywords: Culinary arts; Sartorial traditions; Modern oriya literature